(untitled) (Research, Society and Development, 2021)
Objective: to know the scientific production on health care actions and promotion of fatherhood for men-fathers during the prenatal period, nationally and internationally. Method: integrative review conducted in the CINAHL, SCOPUS, LILACS and MEDLINE databases. The guiding question of the study followed the PICo strategy: What do scientific productions say about health care actions for men-fathers and the promotion of fatherhood during the prenatal period? Inclusion criteria: complete scientific articles, published in Portuguese, English, and Spanish, that addressed the theme of health care actions for men-fathers and the promotion of fatherhood with online and free access, between the years 2010 and August 2020. Exclusion criteria: gray literature, duplicate articles, or articles that didn’t address the research theme. Results: the studies point out that health actions for men are focused on reproductive planning, specifically in obtaining contraceptive methods and also in screening for sexually transmitted infections. It is emphasized that the man-father is still a coadjuvant of care, focusing on the mother-baby binomial. Conclusion: The scientific productions report that men-fathers are in majority in the actions of reproductive planning, but there is no articulation with the prenatal of the partner, and care for his health. Difficulties and strategies for inclusion of this population are listed in the studies.